Evaluasi Manajemen Teknologi Informasi Menggunakan Framework COBIT 5 Domain Monitoring, Evaluate, and Assess pada PT. PLN (Persero) Kantor Pusat - Septian Rachmat Widayanto; Suprapto Suprapto; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT. PLN Persero (Pembangkit Listrik Negara) is an agency of a State-Owned Enterprise that conduct electricity supply business for public interest in an amount and adequate quality and fosters profits and implements Government assignments in the field of electricity in order to support development by applying the principles of Limited Liability Company. PT. PLN (Persero) Kantor Pusat utilizing information technology in supporting its operational activities to be interconnected between IT Fields under the auspices of the STI Division that can support the Company's business processes value to services from the Company's business processes. However, in the implementation there are still problems, namely the use of a supporting document hasn't been maximized which has resulted in the implementation didn't running well or being hampered which makes human resources less understanding of the use of the system and management of information system development management in the Information Technology and Systems Division. From these constraints it's necessary to evaluate information technology management using the framework COBIT 5 domain MEA (Monitoring, Evaluate, and Assess)on PT. PLN (Persero) Pusat. The results of average Capability Level measurement study reach to Level 2 Managed Process and have a GAP average of 1.